The relationship between diet quality indices and odds of breast cancer in women: a case-control study - Mohammad Hassan Sohouli; Genevieve Buckland; Cain C. T. Clark; Heitor O. Santos; Felipe L. Athayde; Vahid Sanati; Leila Janani; Akram Sadat Sajadian; Mitra Zarrati (BMC, 2023)
Abstract Dietary quality is an important factor in the etiology of breast cancer (BrCa), but further studies are required to better elucidate this relationship. Accordingly, we sought to analyze if diet quality, assessed using the Diet Quality Index-International (DQI-I), Mean Adequacy Ratio (MAR), and Dietary Energy Density (DED), was related to BrCa. In this Hospital-based case-control study, 253 patients with BrCa and 267 non BrCa controls were enrolled. Individual food consumption data from a food frequency questionnaire was used to calculate the Diet Quality Indices (DQI). Employing a case-control design, odds ratios (ORs) and 95% confidence intervals (CIs) were obtained, and a dose-response analysis investigated. After adjusting for potential confounders, those in the highest quartile of the MAR index had significantly lower odds of BrCa than those in the lowest (OR = 0.42, 95% CI 0.23-0.78; P for trend = 0.007). Although there was no association between individual quartiles of the DQI-I and BrCa, there was evidence of a significant trend across all the quartile categories (P for trend = 0.030).There was no significant association was found between DED index and the odds of BrCa in the crude and fully adjusted models. We found that higher MAR indices were associated with decreased odds of BrCa, Therefore, the dietary patterns reflected by these scores may serve as a possible guide to preventing BrCa in Iranian women.